Gerald Martin, Gabriel García Márquez. Una vida. Trad. de Eugenia Vásquez Nacarino. Debate, Colombia, 2009; 762 pp. - Díaz Ruíz, Ignacio (Nueva Revista de Filología Hispánica (NRFH), 2011)
Se reseña el libro: Gabriel García Márquez. Una vida.